In vitro propagation of Dendrobium anosmum mutation - Lê , Vinh Thiên; Trương, Thị Ly Na; Nguyễn, Thị Bích Thu; Nguyen, Thi Diem; Nguyễn, Thi Oanh; Nguyễn, Thị Kim Cúc (Hue University Journal of Science: Natural Science, 2022)
Currently, mutant orchids are very interested in orchid lovers who want to collect, but the price of mutant orchids is costly leading to many orchid lovers are unable to own it. This study aims to create mutant orchid plantlets with high quantity and low cost via in vitro propagation method. From the self-pollinated six months old seedpods, we have successfully propagated the orchid mutant seedlings. The results showed that the suitable medium for mutant orchid seed germination and creating protocorm was the basic MS medium supplemented with 0.5 mg/L BA with a rate of up to 93%. The medium for shoot formation and shoot development from protocorm was the best on MS medium added with 1.0 mg/L BA and 0.5 mg/L IBA with a rate of 88%. The rooting induction was 99.06% and the root length reached 5.34 cm with an average of 8.53 roots/shoot when shoots cultured on MS medium supplemented with 1.0 mg/L NAA. The survival rate of in vitro Dendrobium anosmum mutant seedlings after 60 days in the nursery stage was 84.9% on coir and rice husks substrates (1:1).